Does Blockchain for 3D Printing Offer Opportunities for Business Model Innovation?. Issue 4 (3rd July 2020) - Klöckner, Maximilian; Kurpjuweit, Stefan; Velu, Chander; Wagner, Stephan M.
Overview: Blockchain combined with 3D printing offers businesses untapped opportunities. Blockchain can help businesses overcome intellectual property and data security barriers, allowing them to take advantage of emerging 3D printing business models. Specifically, blockchain can facilitate local manufacturing and may lay the groundwork for new business models such as secure design marketplaces and shared factories. Businesses could also improve their value proposition by offering additional services around a printed part, improving value delivery, and offering less costly and more customized products that involve fewer risks. Blockchain could transform the way firms create, deliver, and capture value in 3D printing ecosystems.